Infektiologisch interessierte Urologen werden gebraucht: Nationale Umfrage universitärer Mikrobiologien zur interdisziplinären Zusammenarbeit von Urologie und Mikrobiologie = Nationwide survey among institutes of microbiology in academic medicine : is the interdisciplinary approach the right way to treat patients with urogenital infections? - Schneidewind, Laila; Pelzer, Alexandre E. (Der Urologe, 2017)
Background: Increasing antibiotic resistance is a current and severe problem in medicine, especially in urology. Multidisciplinary antibiotic stewardship programmes are an important approach to counteract increasing resistance rates. This approach includes collaboration between urologists and microbiologists. Objectives: The primary endpoint was to describe the current setting of interdisciplinary work of urologists and microbiologists in university hospitals in Germany. The secondary endpoints were the identification of problems of this interdisciplinary approach in daily routine and implications for the future in patient treatment.Materials and methodsA newly developed, 24-item questionnaire was sent to 34 German microbiology departments at medical universities between June and October 2016; the departments were contacted up to four times. Only complete questionnaires were included in our analysis. Results: The response rate was 50.0%. In the majority of the urological cases a microbiologist was only contacted sporadically and asked for advice, but on the other hand most of the microbiologists think that this contact and discussion about the patient is reasonable and preferable. Of the respondents, 82.4% think that with a consequent interdisciplinary approach there might be lower antibiotic resistance rates in the future. One essential problem of ideal microbial diagnostics and therapeutic advice is that the microbiologist does not receive all relevant information upon request. This might be the case in up to 76.5%. Other problems are of economic nature or shortage of manpower. Conclusion: Interdisciplinary patient care between urologists and microbiologists is reasonable and preferable. This approach has the potential of decreasing antibiotic resistance rates in the future.